PENGARUH PENERAPAN SAK EMKM DAN SIA TERHADAP KUALITAS LAPORAN KEUANGAN UMKM DI KECAMATAN TONDANO SELATAN - Princessa Anastasia Sumual Princessa; Miryam Pingkan Lonto; Tinneke EM Sumual (JAD : Jurnal Riset Akuntansi & Keuangan Dewantara, 2025)
MSMEs are an important sector in the Indonesian economy, but the quality of financial reports is often low due to the suboptimal implementation of SAK EMKM and Accounting Information Systems (AIS). This study aims to analyze the effect of the implementation of SAK EMKM and SIA on the quality of financial reports of MSMEs in South Tondano District. The study used a quantitative approach with a survey method. A sample of 75 MSMEs in the food and beverage sector was determined using the Slovin formula. Primary data were collected through questionnaires and analyzed using validity and reliability tests, multiple linear regression, t-test, and F-test with the help of SPSS version 25. The results of the study indicate that: (1) SAK EMKM has a positive and significant effect on the quality of financial reports (p = 0.041), (2) SIA has a positive and significant effect on the quality of financial reports (p < 0.001), and (3) SAK EMKM and SIA simultaneously have a significant effect on the quality of MSME financial reports (p < 0.001). This study concludes that the implementation of accounting standards and the use of AIS play an important role in increasing the reliability, accuracy, and relevance of MSME financial reports.